INTELLIGENT OPTIMIZATION OF TOOL PATHS TO ACCELERATE THE PRODUCTION OF 3D WOOD DECOR ON CNC MACHINES - Dashkovskyi, Leonid (SWorldJournal, 2025)
Guided by the “technology promotion platform,” manufacturers often prioritize product identity over universal design. However, the transition to standardization does not promote user autonomy but reduces costs. This approach allows for the optimization of